Research on P2P security overlay network model - SUN Zhi-xin1; ZHANG Zhen-wei1; GONG Jing2 (Tongxin xuebao)
To improve the security of software developing and the use of trust mechanism in P2P, a mathematical model of P2P security overlay network was proposed. As the core of the model, overlay network was divided into four parts, including data confirmation layer, data capture layer, trust mechanism layer and routing layer. In the matter of functions, data confirmation layer filtered untrustworthy data; data capture layer run the vectorization of the exchanging data between logic nodes and processed relevant statistics and analysis; trust mechanism layer realized trust mechanism via identifying whether a logic node was trustworthy or not; routing layer build up mapping relationship on logic nodes and physical nodes. To enhance the security of P2P software and the convenience in the use of trust mechanism, simple vector distance classifications and kademlia algorithm were adopted on the basis of the global trust model. Simulating results show that P2P software developing can be more safe and easier under this model.